Public Opinion as an Indicator of Mass Media Social Demand - Rajabov А.Р. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2019)
The article deals with the influence of mass media on the formation and reproduction of national culture and self-consciousness. The purpose of the study is to analyze the existing theories about the influence of the media on the audience and to identify which topics of media messages are most in demand by the population of the Republic of Belarus. The author relies on the results of a sociological study conducted by the Institute of sociology of the NAS of Belarus in determining the sectors important for the economy of Belarus, traces the close relationship of the media with society and notes the problems that most concern the audience. It is concluded that due to its authority and efficiency in reporting the events, the mass media of Belarus is one of the main sources of influence on public opinion.